Everyday communications in religious practices - Gazniuk, L.; Soina, I.; Goncharov, G.; Chervonyi, P. D.; Червоний, П. Д.; ORCID: http://orcid.org/0000-0002-8172-7732 (SHS Web of Conferences 72, 02002 (2019) APPSCONF-2019., 2019)
Встановлено, що розуміння повсякденному житті як соціально певної сфери релігійного життя дозволяє досліджувати релігійні практики православного віруючого, з одного боку, як компонент соціальних відносин і спосіб їх включення в релігійні відносини, інший, як засіб об'єктивізації релігійного досвіду. В рамках різних наукових областей комунікація розглядається як спосіб передачі інформації в міжособистісному, груповому та соціальній взаємодії. Спілкування розглядається як спосіб існування в повсякденному житті, універсальна форма соціальності, відтворена в міжсуб'єктивній взаємодії. Повсякденні відносини православних віруючих характеризуються загальними мовними значеннями та процесами тлумачення. Ідентифікація релігійних людей і співтовариств відбувається за допомогою спілкування. Повсякденне життя є основою спілкування віруючих, релігійна мова є основним фактором характеру рівня повсякденному житті. Показано вплив на розвиток релігійних відносин новітніх засобів спілкування, в тому числі інтернет-форумів, які забезпечують можливість спілкування мирян, духовенства, чернецтва, віруючих інших конфесій і релігій.

It has been determined that understanding everyday life as a socially determined sphere of religious life makes it possible to explore the religious practices of the Orthodox believer, on the one hand, as a component of social relationships and a way of incorporating into religious relations, on the other, as a means of objectifying religious experience. Within the framework of various scientific areas, communication is explored as a way to transfer information in interpersonal, group and social interaction. Communication is considered as a way of being of everyday life, a universal form of sociality, reproduced in intersubjective interaction. The everyday relations of Orthodox believers are characterized by common linguistic meanings and processes of interpretation. The identification of religious individuals and communities takes place through communication. Daily life is the basis of the communication of believers, the religious language is the main factor in the nature of everyday life level. The influence on the development of religious relations of the newest means of communication, including Internet forums, providing the opportunity for communion of the laity, clergy, monastics, believers of other faiths and religions is shown.

Установлено, что понимание повседневной жизни как социально определенной сферы религиозной жизни позволяет исследовать религиозные практики православного верующего, с одной стороны, как компонент социальных отношений и способ их включения в религиозные отношения, другой, как средство объективизации религиозного опыта. В рамках различных научных областей коммуникация рассматривается как способ передачи информации в межличностном, групповом и социальном взаимодействии. Общение рассматривается как способ существования повседневной жизни, универсальная форма социальности, воспроизводимая в межсубъективном взаимодействии. Повседневные отношения православных верующих характеризуются общими языковыми значениями и процессами толкования. Идентификация религиозных людей и сообществ происходит посредством общения. Повседневная жизнь является основой общения верующих, религиозный язык является основным фактором характера уровня повседневной жизни. Показано влияние на развитие религиозных отношений новейших средств общения, в том числе интернет-форумов, обеспечивающих возможность общения мирян, духовенства, монашествующих, верующих других конфессий и религий.
Everyday communications in religious practices / L. Gazniuk, I. Soina, G. Goncharov, P. Chervony // SHS Web of Conferences 72, 02002 (2019) APPSCONF-2019. URL: https://doi.org/10.1051/shsconf/20197202002
Keywords: комунікація; communication; коммуникация; мова; speech; речь; послідовність мови; sequence of speech; последовательность речи; вираз думки; expression of thought; выражение мысли; релігійне спілкування; religious communication; религиозное общение; жест; gesture; жест; притча; parable; притча; символ; symbol; символ